The Psychology of Foreign Fighters. (4th March 2017) - Borum, Randy; Fein, Robert
ABSTRACT: The recent influx of foreign fighters into Syria, particularly those aligning with the Islamic State, has brought renewed attention to the security threat posed by people who cross borders to participate in armed conflict. Although foreign fighters have rarely, if ever, constituted the majority of combatants in a war or insurgency, understanding their role is critical for conflict analysis and prevention. This review focuses on behavioral aspects of the foreign fighter phenomenon. Although other books and articles have focused wholly, or in part, on historical dimensions, the behavioral and social science literature on foreign fighters is much more limited. This review first explores the definitions of "foreign fighter" terminology, then analyzes what is known about their motivations and their pathways toward engaging in armed conflict on foreign soil. It examines recruitment strategies and the role of "radicalization" in feeding the transnational insurgent supply, and finally describes more specifically, the nature of foreign fighter involvement in more recent armed conflicts (e.g., Syria, Chechnya, Iraq, and Afghanistan), and speculates about the prospects for their future involvement.